After war ends a philosophical perspective - May, Larry (Cambridge University Press, 2012)
There is extensive discussion in current Just War literature about the normative principles which should govern the initiation of war (jus ad bellum) and also the conduct of war (jus in bello), but this is the first book to treat the important and difficult issue of justice after the end of war. Larry May examines the normative principles which should govern post-war practices such as reparations, restitution, reconciliation, retribution, rebuilding, proportionality and the Responsibility to Protect. He discusses the emerging international law literature on transitional justice and the problem of moving from a position of war and possible mass atrocity to a position of peace and reconciliation. He questions the Just War tradition, arguing that contingent pacifism is most in keeping with normative principles after war ends. His discussion is richly illustrated with contemporary examples and will be of interest to students of political and legal philosophy, law and military studies.